2014
DOI: 10.1002/pssb.201451340
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission investigation of the Schottky barrier at the Sc/3C-SiC (111) interface

Abstract: The Schottky barrier and interfacial chemistry for interfaces formed by evaporation of Sc onto 3C-SiC (111)-(1x1) surfaces at 600 8C has been investigated using in situ X-ray and ultraviolet photoelectron spectroscopy (XPS and UPS) and low energy electron diffraction (LEED). Sc was observed to grow in a two-dimensional manner and exhibit a (1x1) LEED pattern up to thicknesses of $2 nm beyond which diffraction patterns were no longer observable. XPS measurements of these same films showed a clear reaction of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
1
2
0
1
Order By: Relevance
“…For the clean SiC surface the spectrum is characterized by the broad band in the binding energy region of 0 ÷ 9 eV below E VBM with major peak at ∼2.2 eV. The similar PES result was obtained for the single-SiC(111) surface 18,31 and for the SiC(100) surface. 13 The surface layer of SiC has some number of the Si surface dangling bonds, Si vacancies and Si dimmer-related states which provide the high chemical and adsorption activity of the surface.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…For the clean SiC surface the spectrum is characterized by the broad band in the binding energy region of 0 ÷ 9 eV below E VBM with major peak at ∼2.2 eV. The similar PES result was obtained for the single-SiC(111) surface 18,31 and for the SiC(100) surface. 13 The surface layer of SiC has some number of the Si surface dangling bonds, Si vacancies and Si dimmer-related states which provide the high chemical and adsorption activity of the surface.…”
Section: Resultssupporting
confidence: 77%
“…Recently, the photoemission studies of various SiC polytypes have been reported. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] However, the problems concerning metal/SiC interfaces remain unsolved in many respects to date. There are several studies of adsorption of Cs, 15,16 Na, 17 and Sc 18 metals at the surface of the hexagonal SiC polytype only.…”
mentioning
confidence: 99%
“…Однако проблемы, связанные с интерфейсами металл/SiC, остаются слабо изученными. Существует несколько работ по адсорбции металлов Cs [6], Na [7] и Sc [8] на поверхности гексагонального политипа SiC. Недавно была изучена электронная структура интерфейса Ba/3C-SiC(111) для случая сингулярной поверхности SiC [9].…”
Section: поступило в редакцию 4 декабря 2018 г в окончательной редакции 4 декабря 2018 г принято к публикации 5 декабря 2018 гunclassified
“…Alkali-earth metal and alkali metal adsorbates are good candidates for the formation of metal-semiconductor interfaces and Schottky barrier compositions. The relevant electronic properties were studied for Sc/3C-SiC(111) interface (King et al 2015), Rb and Cs adsorption on graphene on SiC(0001) (Watcharinyanon et al 2011) and Na on graphene on SiC(0001) (Watcharinyanon et al 2012). It was found that Rb, Cs and Na deposited on monolayer graphene samples produce an n-type doping with the electron transfer from the metal to the graphene layer.…”
Section: Introductionmentioning
confidence: 99%